Remade in Hollywood : the global Chinese presence in transnational cinemas - Chan, Kenneth (Hong Kong University Press ; Eurospan [distributor], 2009)
The subjects covered in this volume include the diasporic cinematic gaze on the 1997 Hong Kong handover, Hollywood's response to the Hong Kong handover, the global return of the 'Wuxia pian', and much more.